Adsorption of 4-chlorophenol from wastewater-based activated carbon prepared from Jatropha seed husks - Ahmed Qaid, F.; Danial Azzahari, A.; Yahaya, A.H.; Yahya, R. (Taylor & Francis, 2016)
The removal of 4-chlorophenol (4-CP) from aqueous solution using activated carbon (AC8) prepared from Jatropha seed husks by potassium hydroxide as activating agent at 800°C was investigated. The AC8 was characterized by Fourier transform infrared spectroscopy and energy dispersive X-ray spectroscopy. Batch adsorption was carried out systematically. Experimental results showed that the removal of 4-CP increased with increase in the contact time, adsorbent dosage, and initial concentration of the 4-CP. The Freundlich model was a more suitable model for description of the adsorption isotherm than the Langmuir model. The pseudo-second-order model was better used to describe the adsorption kinetics than the pseudo-first-order model. The thermodynamic parameters such as ∆G°, ∆H°, and ∆S° were determined to describe the adsorption process of the system.